2013
DOI: 10.1038/ncomms3593
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of HIV-1 Vif susceptibility and DNA binding in APOBEC3F

Abstract: The human APOBEC3 family of DNA cytosine deaminases serves as a front-line intrinsic immune response to inhibit the replication of diverse retroviruses. APOBEC3F and APOBEC3G are the most potent factors against HIV-1. As a countermeasure, HIV-1 viral infectivity factor (Vif) targets APOBEC3s for proteasomal degradation. Here, we report the crystal structure of the Vif-binding domain in APOBEC3F and a novel assay to assess Vif-APOBEC3 binding. Our results point to an amphipathic surface that is conserved in APO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 53 publications
7
89
1
1
Order By: Relevance
“…The single dCMP molecule binds the A3Bctd surface and makes several contacts with the enzyme, but it is also assisted by crystal lattice contacts involving symmetry-related molecules (see PDB entry 5CQH), and thus the significance of this result should be interpreted conservatively. Nonetheless, the general location and orientation of the bound nucleotide appear consistent with previous models of A3 proteins binding ssDNA substrates (30,34,37,38,61,62). A3Gctd and A3A NMR chemical shift perturbation experiments, as well as mutational analyses of A3Fctd and A3Gctd, although differing in details, all suggest ssDNA binding paths spanning the catalytic domain surface and extending from the active site toward the ␣-helix 6, which overlaps with the crystallographically observed dCMP interacting with Arg-372 from the ␣-helix 6 and Tyr-319/Lys-320 from the N terminus of ␣-helix 4 (A3Bctd data in Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The single dCMP molecule binds the A3Bctd surface and makes several contacts with the enzyme, but it is also assisted by crystal lattice contacts involving symmetry-related molecules (see PDB entry 5CQH), and thus the significance of this result should be interpreted conservatively. Nonetheless, the general location and orientation of the bound nucleotide appear consistent with previous models of A3 proteins binding ssDNA substrates (30,34,37,38,61,62). A3Gctd and A3A NMR chemical shift perturbation experiments, as well as mutational analyses of A3Fctd and A3Gctd, although differing in details, all suggest ssDNA binding paths spanning the catalytic domain surface and extending from the active site toward the ␣-helix 6, which overlaps with the crystallographically observed dCMP interacting with Arg-372 from the ␣-helix 6 and Tyr-319/Lys-320 from the N terminus of ␣-helix 4 (A3Bctd data in Fig.…”
Section: Discussionsupporting
confidence: 70%
“…A3Gctd and A3A NMR chemical shift perturbation experiments, as well as mutational analyses of A3Fctd and A3Gctd, although differing in details, all suggest ssDNA binding paths spanning the catalytic domain surface and extending from the active site toward the ␣-helix 6, which overlaps with the crystallographically observed dCMP interacting with Arg-372 from the ␣-helix 6 and Tyr-319/Lys-320 from the N terminus of ␣-helix 4 (A3Bctd data in Fig. 5; prior studies with other family members (30,34,37,38,61,62)). Curiously, this nucleotide-binding site on the A3Bctd surface is accessible even when the active site is in the closed conformation.…”
Section: Discussionmentioning
confidence: 99%
“…4A, right panels). A recent study (67) revealed new determinants of Vif binding in the A3F-CTD: Glu-316, Ser-320, and Glu-324. These residues were shown to be part of a negatively charged interface that is directly involved in Vif binding.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of four subspecies of African green monkey, it has been shown that APOBEC3G is adaptively diversifying within hosts because of the antagonism-driven coevolution between Vif and APOBEC3G (397). In addition to APOBEC3G, Vif binds to other proteins in the human APOBEC3 family (e.g., APOBEC3C [398,399] and APOBEC3F [43,400]). Alanine-scanning analyses revealed six Vif residues (D14, R15, M16, W79, D172, and W174) in three conserved motifs that are essential for the degradation of APOBEC3C and APOBEC3F (401).…”
Section: Vif-apobec3g-integrase Associationmentioning
confidence: 99%